Energy plants as biofuel source and as accumulators of heavy metals - Nikolić Magdalena; Tomasević Vladimir; Ugrinov Dragan (Hemijska Industrija, 2022)
Fossil fuel depletion and soil and water pollution gave impetus to the development of a novel perspective of sustainable development. In addition to the use of plant biomass for ethanol production, plants can be used to reduce the concentration of heavy metals in soil and water. Due to tolerance to high levels of metals, many plant species, crops, non-crops, medicinal, and pharmaceutical energy plants are well-known metal hyperaccumulators. This paper focuses on studies investigating the potential of Miscanthus sp., Beta vulgaris L., Saccharum sp., Ricinus communis L. Prosopis sp. and Arundo donax L. in heavy metal removal and biofuel production. Phytoremediation employing these plants showed great potential for bioaccumulation of Co, Cr, Cu, Al, Pb, Ni, Fe, Cd, Zn, Hg, Se, etc. This review presents the potential of lignocellulose plants to remove pollutants being a valuable substrate for biofuel production. Also, pretreat-ments, dealing with toxic biomass, and biofuel production are discussed.